'There Must Be Consequences': The Impact of Misaligned Behaviour Management Perspectives in Remote Indigenous Education. Issue 3 (27th May 2017) - Mackie, Ian; MacLennan, Gary; Shipway, Brad
ABSTRACT: This article argues for a rejection of approaches to school discipline which are rooted in behaviourism and Humean notions of causality. An alternative approach is called for, one that draws upon critical realism to sustain an interdisciplinary depth-realism explanation of the causal mechanisms at play in Indigenous students' struggles for emancipation. The critical realist metaReality approach to spirituality (secular or religious) – suggests a deeper reality in which we are all intimately connected. As such, the freedom of each is necessarily dependent on the freedom of all. This provides us with an alternative way for students and staff to interact which should be seriously considered by schools and their communities. We argue that metaReality, and a respect for the virtues of Indigenous culture, rooted as it is in spirituality, offers the potential to avoid many of the recalcitrant problems of discipline in Indigenous education.